Optimasi Pemotongan Besi Tulangan Pada Pekerjaan Struktur Menggunakan Metode Linear Programming - Jajang Atmaja; Fauna Adibroto; Nurul Hidayah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
In construction projects, reinforcing iron is a very important material in the implementation of construction work. The remaining iron material cannot be avoided in the field, so the figure for the remaining unused material affects the costs incurred by the contractor. Given that iron material is one of the materials with a high price on the market. One solution to reduce the amount of remaining iron material is to optimize iron cutting to get the number of pieces as needed with minimal cutting. The method used is Linear Programming with the help of the Solver Add-In program in Microsoft Excel. The research was conducted on a 3-storey building construction project, namely Puskesmas Kampung Dalam, Kab. Padang Pariaman. Works that reflect iron work on the upper and lower structures. The analysis results were obtained from 7.31% and cost Rp. 27.067.887,-. for the ironworks reviewed. So that the use of the Linear Programming method in the case study of this research is able to optimize the remaining iron material quite well and produce minimum remaining reinforcing iron.